Decompression vs. Decomposition: Distribution, Amount, and Gas Composition of Bubbles in Stranded Marine Mammals - Bernaldo de Quirós, Yara; González-Díaz, Óscar; Arbelo, Manuel; Sierra, Eva; Sacchini, Simona; Fernández, Antonio (Frontiers in Physiology, 2012)
Gas embolic lesions linked to military sonar have been described in stranded cetaceans including beaked whales. These descriptions suggest that gas bubbles in marine mammal tissues may be more common than previously thought. In this study we have analyzed gas amount (by gas score) and gas composition within different decomposition codes using a standardized methodology. This broad study has allowed us to explore species-specific variability in bubble prevalence, amount, distribution, and composition, as well as masking of bubble content by putrefaction gases. Bubbles detected within the cardiovascular system and other tissues related to both pre- and port-mortem processes are a common finding on necropsy of stranded cetaceans. To minimize masking by putrefaction gases, necropsy, and gas sampling must be performed as soon as possible. Before 24 h post mortem is recommended but preferably within 12 h post mortem. At necropsy, amount of bubbles (gas score) in decomposition code 2 in stranded cetaceans was found to be more important than merely presence vs. absence of bubbles from a pathological point of view. Deep divers presented higher abundance of gas bubbles, mainly composed of 70% nitrogen and 30% CO2, suggesting a higher predisposition of these species to suffer from decompression-related gas embolism.